2006
DOI: 10.1063/1.2393165
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy of vertically aligned α-Fe2O3 nanowire array

Abstract: Vertically aligned Fe2O3 nanowire arrays were synthesized by the thermal oxidation of Fe foil. They consist of single-crystalline rhombohedral α-Fe2O3 nanocrystals grown along the [112¯0] direction. Most of the nanowires have a sharp tip (diameter=50nm) and beltlike base. The magnetization measurement reveals a Morin temperature of 125K and unique magnetic anisotropy due to the easy axis of the magnetocrystalline anisotropy perpendicular to the nanowire axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 29 publications
5
58
1
Order By: Relevance
“…The higher relative intensity of the ͑110͒ diffraction peak indicates that ͓110͔ is the preferential nanowire growth direction, in agreement with our HR-TEM results and other studies of ␣-Fe 2 O 3 nanowires and nanobelts grown by thermal oxidation of iron. 18,19 Such preferential orientation is progressively lost when the treatment temperature is increased and wider structures with other morphologies begin to grow on the surface of the pellets. In particular, the relative weight of the ͑116͒ and especially the ͑104͒ reflections increases in XRD patterns ͓Fig.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…The higher relative intensity of the ͑110͒ diffraction peak indicates that ͓110͔ is the preferential nanowire growth direction, in agreement with our HR-TEM results and other studies of ␣-Fe 2 O 3 nanowires and nanobelts grown by thermal oxidation of iron. 18,19 Such preferential orientation is progressively lost when the treatment temperature is increased and wider structures with other morphologies begin to grow on the surface of the pellets. In particular, the relative weight of the ͑116͒ and especially the ͑104͒ reflections increases in XRD patterns ͓Fig.…”
Section: -3mentioning
confidence: 99%
“…In fact, polycrystalline wires 200 nm in diameter were reported to have T M = 80 K and T N = 350 K, 47 while a T M value of 125 K was reported for single-crystalline nanowires. 19 Anomalies of the luminescence intensity with temperature have been reported in several antiferromagnetic compounds. In particular, Holloway et al [41][42][43] reported changes in the luminescence of MnF 2 and alkali manganese trifluorides at temperatures of about T N / 2 and T N .…”
Section: -5mentioning
confidence: 99%
“…The nanowires or nanobelts preferentially grow along the direction that minimizes their surface energy. Although the surface energy of the [110] orientation is not the highest (de Leeuw & Cooper, 2007), the -Fe 2 O 3 nanoscale crystals preferred to grow along the [110] direction (Cvelbar et al, 2008;Kim et al, 2006;Takagi, 1957). In the crystal structure of -Fe 2 O 3 , the O atoms are close-packed in the (110) planes, the O-rich and Fe-deficient character on the (110) planes is considered to be the driving force for the preferential growth along the [110] direction (Srivastava et al, 2007;Wen et al, 2005).…”
Section: α-Fe 2 Omentioning
confidence: 99%
“…In consideration of the rough surface of the iron substrate as observed in the as-grown samples, it is assumed that nanoscale Fe droplets were formed on the surface of the iron substrate at elevated temperatures, and Fe and O were absorbed into the droplets from the iron substrate and the air, respectively. The -Fe 2 O 3 nanostructures would be formed on the iron surface when the droplets got supersaturated, and the growth would be terminated when the liquid is condensed into the solid state during cooling down (Kim et al, 2006;Yu et al, 2006). The -Fe 2 O 3 nanostructure growth should be controlled by the Fe surface diffusion and supersaturation (Lu & Ulrich, 2005;Takagi, 1957;Ye et al, 2005;.…”
Section: α-Fe 2 Omentioning
confidence: 99%
See 1 more Smart Citation